Differences in Cytokine Production in Human Macrophages and in Virulence in Mice Are Attributable to the Acidic Polymerase Protein of Highly Pathogenic Influenza A Virus Subtype H5N1 - Sakabe, Saori; Takano, Ryo; Nagamura-Inoue, Tokiko; Yamashita, Naohide; Nidom, Chairul A.; Mai thi Quynh Le; Iwatsuki-Horimoto, Kiyoko; Kawaoka, Yoshihiro (The Journal of infectious diseases, 2013)
Background. The pathogenesis of influenza A virus subtype H5N1 (hereafter, "H5N1") infection in humans is not completely understood, although hypercytokinemia is thought to play a role. We previously reported that most H5N1 viruses induce high cytokine responses in human macrophages, whereas some H5N1 viruses induce only a low level of cytokine production similar to that induced by seasonal viruses. Methods. To identify the viral molecular determinants for cytokine induction of H5N1 viruses in human macrophages, we generated a series of reassortant viruses between the high cytokine inducer A/Vietnam/UT3028II/03 clone 2 (VN3028IIcl2) and the low inducer A/Indonesia/UT3006/05 (IDN3006) and evaluated cytokine expression in human macrophages. Results. Viruses possessing the acidic polymerase (PA) gene of VN3028IIcl2 exhibited high levels of hypercytokinemia-related cytokine expression in human macrophages, compared with IDN3006, but showed no substantial differences in viral growth in these cells. Further, the PA gene of VN3028IIcl2 conferred enhanced virulence in mice. Conclusions. These results demonstrate that the PA gene of VN3028IIcl2 affects cytokine production in human macrophages and virulence in mice. These findings provide new insights into the cytokine-mediated pathogenesis of H5N1 infection in humans.